Association of folate and vitamin B12 deficiency with vasovagal syncope: a case-control study. (14th October 2021) - Aminorroaya, A; Tajdini, M; Yunesian, M; Boroumand, M.A; Tavolinejad, H; Yadangi, S; Sadeghian, S; Bozorgi, A; Jalali, A; Vasheghani-Farahani, A
Abstract: Background: Studies demonstrated an association between vitamin B12 deficiency and vasovagal syncope (VVS) in pediatric patients. Moreover, some evidence suggested a pathophysiological role of plasma catecholamines elevation in VVS, which can arise from folate or vitamin B12 deficiency in terms of biochemical pathways. Purpose: We aimed to evaluate the association of folate and vitamin B12 deficiency with VVS in adults. Methods: In this case-control study, adult patients (18–70 years of age) with the diagnosis of VVS based on history and physical examination (2018 ESC guidelines) who underwent a head-up tilt test (HUTT) were included as the case group. The control group comprised age- and sex-matched individuals who participated in a population-based cohort study. The most important exclusion criteria were taking vitamin B12 or folate supplements, carbamazepine and phenobarbital, and a history of bariatric surgeries. Plasma levels of vitamin B12, folate, homocysteine, and thyroid-stimulating hormone (TSH), a possible confounder, were measured by Abbott Diagnostics chemiluminescence kits. We compared categorical variables and continuous variables by Chi-square and t-test, respectively. Logistic regression models were employed for adjusting for possible confounders, including age, sex, and TSH. Results: From February 2020 to February 2021, we screened 157 patients with VVS, of whom 44 patients were included. After matching for age and sex, 44 healthy individuals without a history of syncope were examined as the control group. The mean age was 37.9 years in both groups, with 23 women (52.3%) in each group. Baseline characteristics were comparable across the study groups. There were no significant differences between serum levels of vitamin B12, folate, homocysteine, and TSH, as well as the prevalence of deficiency of folate and vitamin B12 between case and control groups (Table 1), even after adjusting for confounding variables. Serum levels of vitamin B12 were remarkably lower in patients with a lifetime syncopal episodes of ≥3 compared to patients with <3 lifetime attacks (Table 2, P=0.042). This correlation remained statistically significant after adjusting for possible confounders, including age, sex, and TSH by the logistic regression model (P=0.032). Conclusions: In this study, we found that there is no significant difference between the prevalence of folate and vitamin B12 deficiency and serum levels of these vitamins in adult patients with VVS and healthy individuals; however, serum vitamin B12 was significantly lower in patients with recurrent VVS compared to patients with a lower burden of syncopal episodes. Future studies with larger sample sizes are recommended in the recurrent VVS subgroup. Therapeutic implications of these findings should be investigated in randomized-controlled trials. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Iran National Science Foundation